Metaphoric Formulation of Rationality - Hetmański, Marek (Analiza, racjonalność, filozofia religii: Księga jubileuszowa dedykowana Profesorowi Ryszardowi Kleszczowi. Nr 6 (2020), 2020)
Rationality problem is perceived, apart from its ontological, methodological, and epistemological aspects, also from the linguistic perspective. Rationality is considered then as a complex phenomenon in which certain human actions, cognition, and knowledge are named, defined, and conceptualized as “rational”. However this perspective is sometimes accused of relativism, it is argued in the paper that such approach is promising and fruitful for the rationality problem. There are presented arguments and conceptions of the metaphorical describing and attributing selected human actions, cooperations and cognition as rational.